Numerical Tests Research on Mechanical Parameters of Rockmass considering Structural Plane Combination Characteristics. (27th August 2018) - Wei, Jihong; Men, Yan; Sun, Shaorui; Wang, Yajie; Qian, Wei; Shi, Wei
Abstract : It is essential to determine rockmass mechanical parameters in stability assessment. The structural z is the main factor in this regard, and we know little about the relationship between mechanical parameters and multiple structure planes. In this paper, we have conducted a series of numerical tests to obtain mechanical parameters for a dam foundation in Southwest China. The biaxial numerical test was performed based on the discrete element method. This numerical test considers the spacing, types, dip angles, and size effect. We established a relationship of mechanical parameters between small size lab samples and large size field samples. We forecasted the strength parameters for a spillway slope in Southwest China. The dip angle has a significant effect on the slope strength and stability. In this case, the rockmass fracture stress-dip angle curve forms a U-shaped distribution. The X-shaped double structure plane demonstrates severe strength weakening relative to a single structure plane. As structure plane spacing reaches a certain level, its influence on rockmass strength diminishes. The elementary volume of the rockmass for dam foundation analysis is about 4 m × 4 m × 4 m.